Toxicidade e Gatilhos: Um Estudo de Caso em Comunidades do Reddit no Brasil - Piorino, Giovana; Lima, Luiz Henrique Quevedo; Pagano, Adriana Silvina; Silva, Ana Paula Couto da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15984, 2025)
In this work, we aim to understand linguistic features that may indicate potential triggers fostering toxic behavior among users in Portuguese-speaking Reddit communities. Our findings show that discussions involving such triggers tend to concentrate political terms and insults, shift topics more frequently, and make greater use of subordinating conjunctions.